We are the Others: Localising Italians for Italians in Video Games - Pettini, Silvia (The Journal of Specialised Translation, 2022)
In order to promote a debate on Otherness in multimedia interactive entertainment from the perspective of Game Localisation, this paper diachronically explores the linguistic and cultural representation of Italianness as Otherness in the original games and in their Italian localisations from the early stage of gaming in the 1980s to the late 2010s. Accordingly, through the analytical lenses of representation, localisation, of which translation is part, and culturalisation, this paper presents a pilot qualitative study of some of the most emblematic and popular Italian male characters in the last forty years, and contextualises it in the four stages of game localisation history to finally illustrate the influence technology has had on game design and localisation. Findings show that Italy and Italians have always been the object of international othering, occupying important roles originally envisioned as Others in game narratives of very different genres. However, the scope of characterisation and its linguistic and cultural dimension are deeply linked to the technological capacities of gaming platforms, which, through the history of multimedia interactive entertainment, have presented increasingly complex challenges and issues in the localisation, translation and culturalisation of Italians for Italians.